Are International Reserves Enough to Prevent Exchange Market Fluctuatıons? - Özek, Yavuz; Ergür, Halil Oğuzhan (Mehmet ŞENTÜRK, 2022)
The demand for international reserves, which is seen as an important tool in eliminating the negative effects of sudden and unexpected situations that may occur in the financial markets, has increased with the phenomenon of globalization. Determining the opportunity cost of reserve accumulation and the correct management of the held reserves are especially important for developing countries. In this study, the relationship between international reserves and the nominal exchange rate is examined using the data for the period of January 2005-January 2022, together with the transition to explicit inflation targeting in the Turkish economy. According to the results, no causality from international reserves to nominal exchange rate was found in traditional causality tests. On the other hand, in the asymmetric causality test, there is causality from the positive component of the international gross reserves to the negative component of the nominal exchange rate, and from the negative component of the international gross reserves to the positive component of the nominal exchange rate. It has been determined that there is a temporal causality from international reserves to the nominal exchange rate in June-July-August-September of every year after 2009.

Finansal piyasalarda oluşabilecek ani ve beklenmedik durumların yaratacağı olumsuz etkilerin giderilmesinde önemli bir araç olarak görülen uluslararası rezervlere olan talep küreselleşme olgusu ile birlikte artış göstermiştir. Rezerv biriktirmenin fırsat maliyetinin belirlenmesi ve tutulan rezervlerin doğru yönetilmesi ise özellikle gelişmekte olan ülkeler için önem arz etmektedir. Bu çalışmada, Türkiye ekonomisinde açık enflasyon hedeflemesine geçiş ile birlikte Ocak 2005-Ocak 2022 dönemine ait veriler kullanılarak uluslararası rezervlerin nominal döviz kuru üzerindeki ilişkisi incelenmektedir. Elde edilen sonuçlara göre, geleneksel nedensellik testlerinde uluslararası rezervlerden nominal döviz kuruna doğru nedensellik bulunmamıştır. Öte yandan asimetrik nedensellik testinde ise uluslararası brüt rezervlerin pozitif bileşeninden nominal döviz kurunun negatif bileşenine doğru, uluslararası brüt rezervlerin negatif bileşeninden nominal döviz kurunun pozitif bileşenine doğru nedensellik bulunmaktadır. Zamansal olarak 2009 yılından sonra her yılın Haziran-Temmuz-Ağustos-Eylül aylarında uluslararası rezervlerden nominal döviz kuruna doğru nedensellik olduğu tespit edilmiştir.
Uluslararası Rezervler Döviz Piyasalarındaki Dalgalanmaları Önlemede Yeterli midir?
Keywords: Economics; Ekonomi